PEMILIHAN BENTUK TAJUK POHON DAN PERDU YANG MENDUKUNG TAMPILAN TAMPAK BANGUNAN, STUDI KASUS BANGUNAN TANOTO FORESTRY INFORMATION CENTER IPB, BOGOR - RAHMAT REJONI (Faktor Exacta, 2017)
Selection of plants in accordance with the appearance of the building is very necessary at this time, this is due to lack of attention to the selection of plants in the design of a building. So in addition to reducing the aesthetic appearance of the building can also reduce the indoor comfort caused by the heat from the sun can directly affect the skin of the building. One method of approach in measuring aesthetics in the science of architecture is to use the approach of Scenic Beauty Estimation (SBE) and Semantic Differential (SD). Visual evaluation produced by the method is calculated quantitatively by SBE method so that it can be assessed in accordance with the perception of the respondents. The aesthetic qualities of a visible building can be strongly influenced by the presence of landscape elements in the form of combinations of trees and shrubs appropriate and dynamic. Using a header shaped form terraced and with a blend of shrub topiary with teh-tehan shrubs. This is because the combination of these plants are dynamic, and can strengthen the character of the building.